2019
DOI: 10.3390/f10060471
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Coarse Woody Debris with Random Forest Classification of Centimetric Aerial Imagery

Abstract: Coarse woody debris (CWD; large parts of dead trees) is a vital element of forest ecosystems, playing an important role in nutrient cycling, carbon storage, fire fuel, microhabitats, and overall forest structure. However, there is a lack of effective tools for identifying and mapping both standing (snags) and downed (logs) CWD in complex natural settings. We applied a random forest machine learning classifier to detect CWD in centimetric aerial imagery acquired over a 270-hectare study area in the boreal fores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…We created a visible-CWD (vCWD) raster image over the study area by processing aerial images as well as LiDAR data via a GEOBIA workflow, involving machine-learning "random forest" supervised classification. This process was described in detail by Lopes Queiroz et al [12]. All spectral bands from the orthomosaic and the NDVI layer, generated with the 2017 mission data, were used to segment the study area into image-objects using eCognition [35].…”
Section: Geographic Object-based Image Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…We created a visible-CWD (vCWD) raster image over the study area by processing aerial images as well as LiDAR data via a GEOBIA workflow, involving machine-learning "random forest" supervised classification. This process was described in detail by Lopes Queiroz et al [12]. All spectral bands from the orthomosaic and the NDVI layer, generated with the 2017 mission data, were used to segment the study area into image-objects using eCognition [35].…”
Section: Geographic Object-based Image Analysismentioning
confidence: 99%
“…The spatial, spectral and height attributes of these objects were used as predictor variables to train a RF classifier, which was applied to the whole study area in three processing chunks that were later merged together. More details of the reference dataset, as well as about the process used to test and apply the classifier can be found in Lopes Queiroz et al [12], who reported completeness between 76.9% and 81.5% and correctness between 75.8% and 87.0% for logs in the study area. Completeness is defined as the percentage of true positives relative to all positives in reference data and correctness is defined as a percentage of true positives relative to all positives in testing data.…”
Section: Classifier Training and Applicationmentioning
confidence: 99%
See 2 more Smart Citations
“…Challenges in CWD field sampling techniques (Ståhl et al 2001;Woldendorp et al 2004), as well as the relevance of dead wood in a host of forest ecosystem functions (Woodall et al 2019), have sparked an interest in applying remotely sensed data for this purpose. For example, CWD objects have recently been detected with encouraging results using LiDAR point clouds (Polewski et al 2015;Joyce et al 2019), aerial photography by means of Unmanned Aerial Vehicles (UAV) (Inoue et al 2014;Duan et al 2017;Panagiotidis et al 2019), or using LiDAR combined with multispectral aerial photography (Richardon and Moskal 2016;Stereńczak et al 2017;Lopes Queiroz et al 2019). Alternatively, models can be established leveraging spectral and structural relationships between plot-level observations of CWD volume and LiDAR or winter Landsat scenes (Sumnall et al 2016;Wolter et al 2017).…”
Section: Remote Sensing Of Coarse Woody Debrismentioning
confidence: 99%